Correlation Analysis of Macular Function and Peripapillary Retinal Nerve Fiber Layer Thickness Following Successful Rhegmatogenous Retinal Detachment Surgery - María D. Díaz-Barreda; Ana Boned-Murillo; Isabel Bartolomé-Sesé; María Sopeña-Pinilla; Elvira Orduna-Hospital; Guisela Fernández-Espinosa; Isabel Pinilla (Biomedicines)
Objectives: In this study, the objective was to assess the correlation between macular function and peripapillary retinal nerve fiber layer (pRNFL) thickness following successful rhegmatogenous retinal detachment (RRD) surgery, as well as the subsequent recovery of visual acuity. Methods: This was a cross-sectional study including 64 eyes from patients with RRD who underwent successful treatment with 23G pars plana vitrectomy (PPV), endophotocoagulation and sulfur-hexafluoride (SF6) were included and compared to a control group consisting of 136 healthy eyes. A complete ophthalmological examination was performed on all participants, including assessment of macular sensitivity using macular integrity assessment (MAIA) microperimetry and pRNFL thickness using DRI-Triton swept-source (SS)–optical coherence tomography (OCT). Results: In the RRD group, retinal sensitivity was decreased. The temporal (T) sector of the total retina (TR) protocol was thicker, while the superior (S) and inferior (I) sectors of the pRNFL protocol were thinner. Within the RRD group, positive correlations were observed between the nasal (N), I sectors and total thickness of TR protocol and MAIA inferior outer (IO) sector; the I sector and total thickness of the TR protocol and MAIA inferior inner (II) sector; the I sector of the pRNFL protocol and MAIA IO sector. Negative correlations were shown between the S, T sectors and total thickness of the pRNFL protocol and MAIA central (C) sector; the N sector and total thickness of the pRNFL protocol and MAIA central temporal (CT) sector. Conclusions: RRD leads to a decrease in pRNFL thickness accompanied by reduced macular sensitivity. These changes may be attributed to factors such as the specific location of the RRD, the distribution pattern of the RNFL and the chosen surgical approach.